Notice of a Runic Door from Iceland, ornamented with Carved Dragons and a scene representing the Slaying of a Dragon. With Engravings of the Door (Proceedings of the Society of Antiquaries of Scotland, 1873)
[The journal notes that this paper will be published in the Archaeologia Scotica.]